The Relevance of Surah Makkiyah and Madaniyah in Character Education - Ahmad Hadi Pranoto; Raharjo Raharjo; Lutfiyah Lutfiyah; Abid Nurhuda; Ali Anhar Syi’bul Huda (Faiyadhah | Journal of Islamic Education Management, 2025)
This article explores the relevance of Surah Al-An'ām verses 151-153 (Makkiyyah) and Surah Al-Baqarah verses 261-267 (Madaniyyah) in the context of character education using library research methods. Through literature analysis, this study identifies the ethical and moral values contained in both surahs and how these values can be integrated into the character education curriculum. Surah Al-An'ām emphasizes the importance of morals, justice, and social responsibility, while Surah Al-Baqarah highlights the values of caring, solidarity, and wise management of resources. The results of the study indicate that the application of Qur'anic values in education can strengthen the character of individuals and communities, and contribute to the formation of a more ethical and responsible society. This research is expected to provide insights for educators in implementing these values in educational environments.